Current account balance cyclicality - Afonso, António (2016)
We assess the cyclicality of current account balances for the period 2001Q1-2014Q4, focussing on Portugal and in Germany, as a benchmark. We find that the cyclical component of the current account was positively explained by 3-months Euribor, but negatively by the financial crisis, systemic stress in Europe, employment and compensation of employees. Moreover, the non-cyclical current account was positively affected by the period of the Economic and Financial Adjustment Program and the terms of trade, but negatively influenced by financial integration.